Production of Siam Mutiara Rice in Batu Merah Village, Lampihong District, Balangan Regency - Alfi Maulana; Tuty Heiriyani; Ronny Mulyawan (Warmadewa University Press, 2023)
Rice (Oryza sativa L.) is an important food crop because it produces rice which is a staple food source, as in Indonesia rice is the main commodity in supporting people's food. One of the causes of rice production is the application of fertilizer, the application of fertilizer by farmers in the study area is still general in nature due to limited knowledge of data. This study aims to determine rice production due to the use of inorganic fertilizers in Batu Merah Village, Lampihong District, Balangan Regency. The method used in this research is descriptive quantitative. Data collection on rice production by way of surveys and questionnaires to 10 respondent farmers in the field, to determine the yield of rice production in 10 paddy fields with an average area of ​​study area, around (± 9.7 ha) or 9,798 m2. The farmers used inorganic fertilizers twice, before planting with a dose of 75 kg/ha of urea, 30 kg/ha of SP-36, and 30 kg/ha of NPK fertilizer. The second fertilization when the rice plants are two months old, with a dose of 50 kg/ha of urea, 20 kg/ha of SP-36 fertilizer, and 20 kg/ha of NPK fertilizer. Rice production results from the area of ​​land that has been converted, yields an average of around 2.99 t/ha. The main factor of high and low production yields is due to the different area of ​​paddy fields owned by farmers.